2019
DOI: 10.1080/09589236.2019.1599504
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of teacher education in Finland: subject teachers compared with primary teachers

Abstract: An exit survey performed for graduating students is an economic way to assess the outcomes of teacher education. In this study, exit survey data were collected from eight cohorts of Finnish student teachers who graduated between the years 2008 and 2015. A final sample consisted of 1102 preservice primary and subject teachers. A 10-item scale based on INTASC standards of teacher competency was used to measure graduates' satisfaction regarding the knowledge and experience they had attained. This paper concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The four factors were labelled as 1) Human sciences, 2) Mathematics and natural sciences, 3) Languages, and 4) Artistic and practical subjects. The four-factor model corresponds well with the common way to group subjects in the Finnish curricula (Saloviita 2019). This result confirms the categorisation as having internal rationale or reflects how students are well socialised to think through these categories.…”
Section: Four Subject Groupssupporting
confidence: 75%
See 1 more Smart Citation
“…The four factors were labelled as 1) Human sciences, 2) Mathematics and natural sciences, 3) Languages, and 4) Artistic and practical subjects. The four-factor model corresponds well with the common way to group subjects in the Finnish curricula (Saloviita 2019). This result confirms the categorisation as having internal rationale or reflects how students are well socialised to think through these categories.…”
Section: Four Subject Groupssupporting
confidence: 75%
“…As 95% of the participating student teachers were in at least their fourth year of studying at university, they could be considered to be specialists well aware of the content of the subjects to be taught. Saloviita (2019) found that in general, Finnish student teachers in subject teacher education programmes are satisfied with the level of content knowledge for teaching that they achieved at university.…”
Section: Methodsmentioning
confidence: 95%
“…2. The implementation of good teaching practices can also contribute to the formation of teacher competence (Saloviita, 2019).…”
Section: Teacher Professionalismmentioning
confidence: 99%